Photothermal excitation in non-local semiconductor materials with variable moisture thermal conductivity according to moisture diffusivity - El-Sapa, Shreen; El-Bary, Alaa A.; Chtioui, Houda; Becheikh, Nidhal; Lotfy, Khaled (Frontiers in Materials, 2023)
In this work, a new model is described for the case of interference between thermal, plasma and elastic waves in a non-local excited semiconductor medium. The governing equations have been put under the influence of moisture diffusion in one dimension (1D) when the moisture thermal conductivity of the non-local medium is taken in variable form. Linear transformations were used to describe the dimensionless model. The photo-thermoelasticity theory according to moisture diffusivity was applied to describe the governing equations using Laplace transforms to obtain analytical solutions. In the time domain, complete solutions are obtained linearly when the conditions are applied (thermal ramp type and non-Gaussian plasma shock) to the surface through numerical methods of inverse Laplace transforms. Numerical simulation is used to display the basic physical quantities under study graphically. The current research has yielded several specific examples of great significance. Many comparisons are made under the influence of fundamental physical variables such as relaxation times, variable thermal conductivity, non-local parameters, and reference moisture parameters through graphing and describing them theoretically.